Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

Un protocole d'application culturellement pertinent selon les sexes - Association des femmes autochtones du Canada (AFAC) (2011)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; care; cours; discipline; droits des femmes*; droits des femmes* autochtones; féminisme autochtone; histoire et politique; pol4105; premier cycle; périodes historiques; québec; régions géographiques; santé; santé mentale; sciences humaines; sciences sociales; suicide; système colonial; systèmes d'oppressions; thématiques; traumatismes générationnels; travail social; violences

Interventions féministes : parcours et perspectives - De Koninck, Maria; Pâquet-Deehy, Ann; Dennie, Maureen; Savard, Sylvie; Turgeon, Joane (Nouvelles pratiques sociales, 1994)
L'article présente une synthèse des résultats de deux recherches réalisées en concertation et portant sur l'intervention féministe dans les domaines de la santé et des services sociaux au Québec. Recensions d'écrits complétées par une collecte de données auprès d'intervenantes oeuvrant sur le terrain, les recherches ont permis de constater que l'intervention féministe se répand et se diversifie. À partir de ce constat, les auteures proposent des réflexions et soulèvent des questions sur la pertinence, les possibilités et les mécanismes pouvant favoriser la recherche théorique sur la base des pratiques.
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; cours; discipline; intervention sociale; périodes historiques; québec; régions géographiques; santé; santé des femmes*; sciences humaines; thématiques; travail social; trs3500